Iowa Birdline update, May 11-13, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email for the Iowa Birdline update for May 11-13, 1992. Highlights of the update include sightings of a two Red Knots, Snowy Plover, Brown Pelican, a pair of Bewick's Wrens and two singing Henslow's Sparrows. Also included are handwritten notes for the next week's update with sightings of a Townsend's Solitaire and a Swallow-tailed Kite. Epson - sheet feed/flatbed